Electron hopping transport in 2D zinc oxide nanoflakes. (8th February 2017) - Jian, Dunliang; Lai, Jian-Jhong; Lin, Yen-Fu; Zhai, Jianpang; Li, Irene Ling; Tian, Feng; Wang, Shulin; Hua, Ping; Ku, Ming-Ming; Jian, Wen-Bin; Ruan, Shuangchen; Tang, Zikang
Abstract: A sequential hydrothermal process was used to synthesize ZnO nanostructures on Si substrates. The synthesized ZnO nanostructures were inspected and presented a morphology of 2D structures, named nanoflakes. These ZnO nanoflakes had a thickness of tens of nanometers. An energy dispersive x-ray spectrum revealed their composition of only Zn and O elements. In addition, its crystalline structure was investigated by high-resolution transmission electron microscopy. The nanoflakes were then dispersed for another morphology measurement using atomic force microscopy and their average thickness was determined. The dispersed nanoflakes were further contacted with metal electrodes for electron transport measurements. Through the analysis of temperature-dependent resistivity, it was confirmed that the electron transport in such ZnO nanoflakes agrees well with the theory of Mott's 2D variable range hopping. The nature of the 2D electron system in the ZnO nanoflakes points to potential applications of this 2D semiconductor as a new channel material for electronics.